Identification of Novel and Recurrent Variants in MYO15A in Ashkenazi Jewish Patients With Autosomal Recessive Nonsyndromic Hearing Loss - Booth, Kevin T.; Hirsch, Yoel; Vardaro, Anna C.; Ekstein, Josef; Yefet, Devorah; Quint, Adina; Weiden, Tzvi; Corey, David P. (Frontiers in Genetics, 2021)
Hearing loss is a genetically and phenotypically heterogeneous disorder. The purpose of this study was to determine the genetic cause underlying hearing loss in four Ashkenazi Jewish families. We screen probands from each family using a combination of targeted mutation screening and exome sequencing to identifiy the genetic cause of hearing loss in each family. We identified four variants in MYO15A, two novel variants never previously linked to deafness (c.7212+5G>A and p.Leu2532ArgfsTer37) and two recurrent variants (p.Tyr2684His and p.Gly3287Gly). One family showed locus heterogeneity, segregrating two genetic forms of hearing loss. Mini-gene assays revealed the c.7212+5G>A variant results in abnormal splicing and is most likely a null allele. We show that families segregrating the p.Gly3287Gly variant show both inter and intra-familial phenotypic differences. These results add to the list of MYO15A deafness-causing variants, further confirm the pathogenicity of the p.Gly3287Gly variant and shed further light on the genetic etiology of hearing loss in the Ashkenazi Jewish population.